Peningkatan Ketahanan Pangan Keluarga Melalui Sosialisasi dan Praktik Aquadalon Lele dan Kangkung di Desa Kemujan, Kecamatan Adimulyo, Kabupaten Kebumen - Alya Febriza Putri; Ameilia Fernanda Puspita Loka; Desinta Zahra Setiani; Evelyne Patricia Ngandiri; Maulina Farah Maynar; Galih Syubhan Syabani; Innova Rijanto; Ajeng Sarwi Lestari; Katira Arofah; Irwan Iftadi (JOURNAL SAINS STUDENT RESEARCH, 2026)
Limited yard space and the increasing demand for household food are challenges in strengthening family food security in Kemujan Village. This Community Service Program (KKN) aims to optimize the utilization of narrow land through the Aquadalon (Aquaponics in a Gallon) innovation, an integrated cultivation system of catfish (Clarias sp.) and water spinach (Ipomoea aquatica) using modified recycled gallon containers. The implementation method used a participatory approach through stages of socialization, installation training, hands-on practice, and maintenance assistance for heads of households as the target audience. A total of 30 Aquadalon units were created and implemented as pilot projects. Program evaluation was conducted descriptively through observations of participation levels, installation assembly skills, and the success of fish and plant maintenance. The results showed high enthusiasm among participants, an independent ability to assemble the system, and healthy growth of both water spinach and catfish at the household scale. The Aquadalon system proved to be water-efficient, utilized fish metabolic waste as plant nutrients, and was relatively low-cost. This program has the potential to become a simple, economical, and easily replicable model of appropriate technology to support family food independence in areas with land limitations.